Development of reinforced in-situ anti-corrosion and wear Zn-TiO2/ZnTiB2 coatings on mild steel - O.S.I. Fayomi; A.P.I. Popoola; L.R. Kanyane; T. Monyai (Results in Physics, 2017)
The development of reinforced composite coating has resulted into advanced engineering application because of the exceptional properties and increase service life. In this study, we investigated the effect of Solanum tuberosum (ST) as additive to Zn-TiO2/Zn-TiB2 sulphate bath coating by co-deposition route on mild steel. The structural characteristics and surface profile of the produced coating were examined using scanning electron microscope coupled with energy dispersive spectroscopy (SEM/EDS) and PosiTector (SPG) respectively. The anti-corrosion resistance activities of the deposited coatings were evaluated on a 101 AUTOLAB potentiostat/galvanostat device in a 3.65 wt% NaCl. The wear characteristics of the Zn-TiO2/TiB2 composite coatings were examined on a dry abrasive MTR-300 test rig. The thermal stability of the produced coatings was studied in an isothermal furnace at 600 °C and further characterized using a high tech optical microscope. From the results, it was found that Zn-TiO2/Zn-TiB2 were compassed with needle like pattern and perhaps a compact and distinctive structure was found with Zn-TiO2/Zn-TiB2/ST coatings. The microhardness deposited coatings increased with TiO2 and TiB2 interference in the plating bath, more significant improvement was noticed in the presence of natural bath-additive and the addition of ST lead to changes in the morphologies of the composite coatings. A massive decrease in corrosion and wear rate in all coatings produced as against the control sample was noticed. This was attributed to the dispersive strengthening activities of the embedded TiO2/TiB2/ST additive on the bath formed. Keywords: Zn-TiO2/Zn-TiB2, Solanum, Strengthening, Wear, Microhardness